2022
DOI: 10.3390/su14063174
|View full text |Cite
|
Sign up to set email alerts
|

What Reduces Household Food Waste in Japan? Nation-Wide and Region-Specific Contributing Factors in Urban and Rural Areas

Abstract: We analyze the contributing factors (i.e., attribute factors and behavioral factors) that lead to household food waste in Japan by region (i.e., large cities, small cities, and villages) using a nationwide sample and an ordered probit model. As a result of the analysis, it was found that “gender”, “age”, “children in the household”, “occupation”, “safety awareness”, and “time” were related to the occurrence of food waste in terms of consumer attributes, which were common throughout Japan. In terms of consumer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 23 publications
3
17
0
Order By: Relevance
“…In summary, cooking behavior tended to partially mitigate the disparity in healthful eating habits due to economic status and spare time. Previous studies suggested positive associations between socioeconomic status, such as economic status and spare time, and dietary habits [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][40][41][42]. Additionally, they illustrated that cooking behaviors can lead to healthful eating habits [20][21][22][23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, cooking behavior tended to partially mitigate the disparity in healthful eating habits due to economic status and spare time. Previous studies suggested positive associations between socioeconomic status, such as economic status and spare time, and dietary habits [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][40][41][42]. Additionally, they illustrated that cooking behaviors can lead to healthful eating habits [20][21][22][23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…The participants used five choices to rate subjective spare time, namely, somewhat much, neither, somewhat less, and less [28]. Although subjective spare time was not tested for criterion-related validity, previous studies confirmed a significant inverse association with household food waste [40]. In addition, previous studies reported an association between lack of time and unhealthy eating habits [41,42].…”
Section: Independent Variablesmentioning
confidence: 99%
“…Many of these studies highlighted behaviours that can increase or decrease FW. Meal planning and shopping lists can reduce FW [52][53][54][55][56][57][58][59][60], cooking or serving too much food can increase this phenomenon [26,53,54,[61][62][63] as well as frequency purchase could increase FW [22,58,64].…”
Section: Plos Onementioning
confidence: 99%
“…One study analyzed the factors contributing to food waste in Japanese households using categorizations based on large cities, small cities, and rural areas. The results revealed that individuals with "agricultural experience" had significantly lower rates of food waste in urban and rural areas [25]. Mobile application technology has the potential to reduce food waste.…”
Section: Introductionmentioning
confidence: 99%
“…Research on food loss and waste began in the late 1980s; since 2005, research on this issue has become more widespread globally [9]. In recent years, research on food waste at the consumer end has mainly focused on five areas; anti-food waste policies and methods [10][11][12][13], quantity measurements of household food waste [14][15][16][17][18], analyses of the harms of food waste [18][19][20], analyses of the factors influencing household food waste [21][22][23][24][25][26], and methods and techniques to deal with food waste [27,28]. In the area of anti-food waste, a study on anti-food waste policies explored the influencing factors of policy implementation and found that the effective implementation of policies is closely related to the active participation of supermarket managers.…”
Section: Introductionmentioning
confidence: 99%